The Relationship Between Parents’ Income and the Level of Anxiety Nursing Student of Klabat University During Covid-19 Pandemic - Weol, Wulan Intan Melati; Rantepadang, Andreas (8ISC Abstract Proceedings, 2022)
The COVID-19 pandemic has influenced many aspects of life, such as in the health sector, including mental health issues. Students may experience some mental health issues, and anxiety may be one of them, and the causative factor could be a concern about their parents’ financial situation. This research aimed to determine the relationship between parents’ income and the level of anxiety experienced by students during the pandemic. The study is a quantitative type of research using a cross-sectional design, with statistical tests of Spearman’s rho correlation and purposive sampling technique using 182 samples. The instruments used are the Badan Pusat Statistik Indonesia (BPS) income classification division and the GAD-7 questionnaire (General Anxiety Disorder-7). The results revealed that during the COVID-19 pandemic, the dominant income of students’ parents was very high (29.7%), and student anxiety was mild (42.9%). There is no significant relationship between parents’ income and the level of anxiety of the students of the Faculty of Nursing, Klabat University, during the COVID-19 pandemic (r = 0.024 and p = 0.751). It is recommended that student coping mechanisms need to be maintained or improved. Keywords : The pandemic of COVID-19, Parent’s income, Student’s anxiety